Straight From the Plastome: Molecular Phylogeny and Morphological Evolution of Fargesia (Bambusoideae: Poaceae) - Zhou, Yun; Zhang, Yu-Qu; Xing, Xiao-Cheng; Zhang, Jian-Qiang; Ren, Yi (Frontiers in Plant Science, 2019)
Fargesia is ecologically and economically important in mountainous forests. Many Fargesia species are also important sources of food for some endangered animals such as the giant panda. Recent molecular phylogenetic analyses have revealed Fargesia as a polyphyletic group despite some unclear lineage affinities. In the present study, we reconstructed the phylogeny of Fargesia and its allies, including Thamnocalamus, Arundinaria (incl. Bashania), Yushania, Indocalamus, Ampelocalamus and Phyllostachys, from a plastome sequence matrix that contained 20 Fargesia and five Yushania species as ingroups, 16 species from nine other bamboo genera plus Oryza sativa and Zea mays as outgroups. Fargesia and its allies were broken into eight clades. Several Fargesia species were clustered into the Thamnocalamus clade and the Drepanostachyum + Himalayacalamus clade that rendered the polyphyly of Fargesia. The remaining six clades, including the Fargesia spathe clade, the Phyllostachys clade, Arundinaria fargesii, the Ampelocalamus clade, the Fargesia grossa clade, and the Fargesia macclureana clade, were identified. Molecular phylogenetic analyses supported that Yushania should be included in Fargesia (s.l.) which had synapomorphy of expanded leaf sheaths in varying degree at the basis of inflorescences, and further divided into the Fargesia spathe clade, the Fargesia grossa clade, and the Fargesia macclureana clade. All sampled species of Yushania were nested within the Fargesia grossa clade. The probable model of the origin of the species in the Fargesia spathe clade with spathe-like leaf sheath syndrome was proposed. Moreover, the formation of the spathe-like leaf sheath syndrome may be correlated with cold climatic conditions in Quaternary. Our results provide new sight into the phylogenetic relationship within Fargesia.